A= x(x^3 + y) – x^2(x^2 – y) – x^2(y – 1) tại x= -10 và y= 5

Question

A= x(x^3 + y) – x^2(x^2 – y) – x^2(y – 1) tại x= -10 và y= 5

in progress 0
Kaylee 10 phút 2021-09-16T18:51:34+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-16T18:52:40+00:00

    `A=x(x^3+y)-x^2(x^2-y)-x^2(y-1)`

    `⇔A=x^4+xy-x^4+x^2y-x^2y+x^2`

    `⇔A=x^2+xy`

    `⇔A=x(x+y)`

    `⇔A=(-10)(-10+5)`

    `⇔A=50`

    0
    2021-09-16T18:52:58+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `A= x(x^3 + y) – x^2(x^2 – y) – x^2(y – 1)`

    `=x^4+xy-x^4+x^2y-x^2y+x^2`

    `=xy+x^2=x(x+y)`

    Thay x=-10 và y=5 ta có

    `A=-10×5=-50`

    học tốt nhé^^

    IQ vô cực^^

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )